DEITIC AND NUMERATIVE ELEMENTS IN IRON MAN MOVIE SCRIPTS - Nadeak, Maria Novtalia Uli (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2019)
This article explains numerative and deitic elements of nominal ellipsis in the three sequels of Iron Man Movie Scripts. Iron Man movie was chosen because Iron Man was an interesting science fiction movie at that time. In previous articles, Ellipsis had been analyzed in some novels and they only discussed the meaning and the general type of ellipsis. In order to fill the gap, this article describes the numerative and deitic elements of nominal ellipsis.In this focus, the syntactical unit found in the Iron Man movie scripts was analyzed based on the theory of nominal ellipsis by M.A.K Halliday and Ruqiyah Hasan (1974:143). Numerative element itself has two types: cardinal and ordinal numerative. Cardinal means that the reference is roman numbering (one, two, three, etc), and ordinal numerative is a number of steps (first, second, third, etc). Deitic is normally a determiner. Deitic has divided into specific deitic and non-specific deitic. Specific deitic means the marker is included into specific thing like possessive (such as my, your), demonstrative (such as that, this), and determiner (the). Furthermore, non-specific means that the marker of nominal ellipsis are unclerly explain like both, each, every, any, either, no, and neither.